(untitled) (Comprehensive Journal of Science, 2026)
The study aims to identify the reality of international reserves in terms of the size of the structure and development of these reserves and their adequacy in the Libyan economy. It can be achieved the aim of this study by of Inter receives, end by measuring and determining the impact of important economic variables on international reserves in the Libyan economy during the time period (1980-2019). By applying autoregressive distributed lagged dependent variable (ARDL).The empirical estimating reached a set of results; The most important of mortal results. which is the existence of an equilibrium relationship between international reserves and the study variables in the short to long term. The study recommends the necessity of taking into consideration the issue of international reserves and directing them in supporting economic development paths and investing them in productive projects and protecting them from erosion, and benefiting from the accumulation of international reserves in a manner that leads to diversification in the domestic and foreign sources of income for the national economy.